Kompetensi Guru Pendidikan Agama Islam Perspektif Imam An-Nawawi Dalam Kitab Al-Tibyan Fii Adaabi Hamalatil Quran (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This research is motivated by the emergence of problems that occur in the world of education, especially in terms of low competence and teachers' lack of attention to their obligations in educating. The deviations that occur have even reached a fatal level, starting from slapping, harassment, and even being tortured to death. So the solution is to re-study and refer to the books of the ulama, because they are the role models in this life, one of which is in the world of education. One book that can be used as a reference is the book at-Tibyan Fii Adaabi Hamaltil Quran written by Imam An-Nawawi. This research aims to explore Imam An-Nawawi's thoughts regarding the competency of PAI teachers in the At-Tibyan book and its relevance to today's education. This research uses qualitative methods with a type of literary study approach obtained from various literature such as journals, books and relevant scientific works, in analyzing data using content analysis techniques. The main data for this research is the book at-Tibyan Fii Adaabi Hamalatil Quranwritten by Imam An-Nawawi. The results of this research indicate that there is a suitability of Imam An-nawawi's thoughts in the At-Tibyan book with current contemporary education. This means that it is relevant to the Regulation of the Minister of Religion of the Republic of Indonesia Number 16 of 2010 concerning the Management of Religious Education in Schools.
Keywords: Competence; PAI Teacher; At-Tibyan Book; Imam An-Nawawi